Lee Hayman's Steinbeck room - Art Ring:::Creator::::::::::::
Lee Richard Hayman's Steinbeck room. Mr Hayman was devoted collector who, in 2004, donated 125 boxes of these materials to the Martha Heasley Cox Center for Steinbeck Studies. Digital copy only. No hard copy.